Hubungan Karakteristik Sosiodemografi dengan Hasil Terapi Tuberkulosis Paru di RSUD Banyumas - Shavira, Rurynta Ferly; Restinia, Mita; Nurmeilis, Nurmeilis; Maula, Charisma Soffa (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Pulmonary tuberculosis (TB) is one of the infectious diseases caused by Mycobacterium tuberculosis and is one of the highest causes of morbidity and mortality rates with a low level of treatment outcome. Indonesia is the second country in the world with the largest tuberculosis burden. This study aims to determine the relationship of sociodemographic characteristics with the results of pulmonary tuberculosis therapy at Banyumas Regional Public Hospital for the period 2019-2021. This study used a case-control method. The inclusion criteria in this study were new pulmonary tuberculosis patients at the Banyumas Regional Public Hospital and patients aged ≥18 years, both male and female.  Multi-drug resistance (MDR) TB patients and patients with incomplete medical record data were excluded. There were 166 patients enrolled in this study. Data analysis was performed by univariate analysis and bivariate analysis by chi-square test. The results showed that the sociodemographic characteristics were dominated by male patients (57,2%), patients aged <65 years (66,3%), patients weighing <55 kg (53%), not graduating from college (94%), currently working (64,5%), married (68,7%), have health insurance (94%), and close distance (<10 km) to the hospital (53%). The conclusion is that gender ((P=0,028; OR 2,112; 95%Cl(1,129 – 3,951)), age (P=0,014; OR 2,413; 95% Cl (1,242 – 4,689)), body weight (P=0,000; OR 3,306; 95%Cl (1,748 – 6,252)), and distance from the patient's house to the hospital (P=0,020; OR 2,190; 95% CI (1,176 – 4,077)) have a significant relationship with the outcome of pulmonary TB therapy at Banyumas Regional Public Hospital.